Chronic Obstructive Pulmonary Disease Prevalence and Associated Factors in a Setting of Well-Controlled HIV, A Cross-Sectional Study. (3rd May 2020) - Kayongo, Alex; Wosu, Adaeze C.; Naz, Tasmia; Nassali, Faith; Kalyesubula, Robert; Kirenga, Bruce; Wise, Robert A.; Siddharthan, Trishul; Checkley, William
Abstract: In Sub-Saharan Africa, COPD remains prevalent but its association with HIV is not well characterized especially in rural settings. We assessed for COPD prevalence, associated factors and lung function profile among HIV-infected individuals attending ART clinics in rural Nakaseke district of Uganda. We enrolled HIV-positive participants from four HIV treatment centers in rural Uganda. Participants underwent spirometry testing following standard guidelines. We defined COPD as a post-bronchodilator FEV1 /FVC ratio less than the fifth percentile of the NHANES III African-American reference. We assessed for factors associated with COPD and lung function profiles using multivariable logistic and linear regression analyses. We analyzed data from 722 HIV-positive participants (mean age 48.0 years, 59.7% women). Over 90% of participants were on ART for a median duration of 4 years (IQR 2–7 years), with a median viral load of 0 copies/mL (IQR 0–0 copies/mL), current and baseline CD4 + T cell count of 478 cells/mm 3 (IQR 346–663 cells/mm 3 ) and 335 cells/mm 3 (IQR 187–523 cells/mm 3 ) respectively. The prevalence of COPD was 6.22%. COPD was associated with worse respiratory symptoms and health status. History of pulmonary tuberculosis was strongly associated with COPD (adjusted OR = 4.92, 95% CI 1.71 to 14.15, p = 0.003) and reduced lung function. Use of ART, CD4 +T cell count and viral load were not associated with COPD or reduced lung function. In conclusion, we report a COPD prevalence of 6.22% in HIV-infected individuals in rural Uganda. Pulmonary tuberculosis remains the strongest predictor of COPD risk and reduced lung function in well-controlled HIV.